DESTINASI: Kolaborasi Kreatif Musik Digital, Puisi dan Tari - Junita Batubara (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2021)
This research discusses the implementation of a music score into a collaboration of digital music, dance and poetry. The integration of the three arts is done by symbolizing human life from birth to adulthood. The researcher, as the creator of this Destination composition, intends to add to his repertoire by combining three different arts, namely, digital music, dance and poetry. This compositional work was created using qualitative, practice-based, practice-led and ethnographic methods. The process of making this work is by analyzing music score data taken from the results of field exploration and in combination with poetry and dance script data and then processed into the laboratory desk. The result is the creation of collaborative digital music, dance and poetry, based on the culture of human life and the author's background and life experiences. The work reflects the symbols of human life which are revealed in the poem entitled Directions of Life. Initially, Destination's composition work was a composite work created using cross-cultural (combination) elements of Western music, and Malay music (gendang Malay). Furthermore, the work is processed into a collaboration that is carried out with a combination of motion, emotion, voice intonation and digital music. The result of the collaboration of Destination's compositions is to produce a performance that combines three different arts where music is the main focus in bringing out ideas and concepts of body movement and voice intonation from dancers and poetry readers. The ability to relate ideas or ideas to a musical concept, producing a new work with the collaboration of three different arts which can be used by musicians, practitioners, and educators in Indonesia. Penelitian ini mendiskusikan implementasi  sebuah skor musik menjadi kolaborasi musik digital,seni tari dan puisi. Penggabungan ketiga seni tersebut dilakukan dengan cara symbol kehidupan manusia dari mulai lahir hingga dewasa. Peneliti sebagai pencipta karya komposisi destinatioan ini bermaksud untuk menambah repertoar dengan menggunakan penggabungan tiga seni yang berbeda yaitu, musik digital, tari dan puisi. Karya komposisi ini diciptakan dengan menggunakan metode kualitatif, practice-based, practice-led dan ethnographic. Proses pembuatan karya tersebut dengan melakukan analisa data skor musik yang diambil dari hasil eksplorasi lapangan dan kombinasi dengan data script puisi dan tari kemudian diolah ke dalam desk laboratory. Hasilnya adalah terciptanya kolaborasi karya seni musik digital, tari dan puisi, berdasarkan budaya kehidupan manusia dan latar belakang penulis dan pengalaman kehidupan penulis. Di dalam karya tersebut mencerminkan symbol-symbol kehidupan manusia yang terungkap dalam puisi yang berjudul Arah Kehidupan. Awalnya Karya komposisi Destination merupakan karya penggabungan yang diciptakan menggunakan silang budaya (kombinasi) elemen-elemen musik Barat, dan musik melayu (gendang melayu). Selanjutnya karya tersebut diolah menjadi sebuah kolaborasi yang dilakukan dengan perpaduan gerak, emosi, intonasi suara dan musik digital. Hasil dari kolaborasi karya komposisi Destination adalah menghasilkan sebuah pertunjukan perpaduan tiga ilmu seni yang berbeda dimana musik sebagai fokus utama dalam memunculkan ide-ide dan konsep gerakan tubuh dan intonasi suara dari penari dan pembaca puisi. Kemampuan untuk mengaitkan idea atau gagasan terhadap sebuah konsep musik, menghasilkan sebuah karya baru dengan kolaborasi tiga seni yang berbeda dimana bisa digunakan oleh musisi, praktisi, dan edukator di Indonesia.